Mesonephric-like adenocarcinoma of the uterine corpus with focal sarcomatous differentiation: A case report - Serika Kanao; Makoto Urano; Kazuhisa Fujita; Fumi Utsumi; Kazuhiro Sugihara; Kiyosumi Shibata (Fujita Medical Journal)
Mesonephric-like adenocarcinoma of the uterine corpus was first reported in 2016, and added as a new item to the 5th edition of the WHO classification in 2020. It accounts for approximately 1% of patients with uterine corpus cancer, being rare. The histology of this carcinoma varies, making pathological diagnosis difficult. A diagnosis is made at an advanced stage in comparison with other histological types of uterine corpus cancer, and the prognosis is reportedly poor with high-level malignancy. In addition, there are few case reports of mesonephric-like adenocarcinoma of the uterine corpus with sarcoma. In this study, we report a patient in whom preoperative chemotherapy was performed under a diagnosis of cervical carcinoma, but the resected specimen led to a diagnosis of sarcomatous component-mixed mesonephric-like adenocarcinoma of the uterine corpus after surgery.